Can a sustainable agriculture policy lead to improved human well-being? : Reflections on the book Sustainable Agriculture Policies for Human Well-being. Integrated Efficiency Approach by B. Czyżewski and Ł. Kryszak, Springer 2022. - Kowalczyk, Stanisław; Sobiecki, Roman (Economics and Environment, 2023)
This paper is a scientific review of Czyżewski and Kryszak's book entitled Sustainable Agriculture Policies for Human Well-being. Integrated Efficiency Approach (2022). The work concerns one of the most important issues today, which is the sustainability of economic development, including the sustainability of agriculture and the consequences of such a process for current and future generations. This paper presents the main views and findings of the Authors of the reviewed book. It also includes their confrontation with other researchers' views, including this paper's authors.